2020
DOI: 10.3847/1538-4357/ab8db4
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Broadband Temporal Features Observed in the Black-hole Transient MAXI J1820+070 with Insight-HXMT

Abstract: We study the evolution of the temporal properties of MAXIJ1820+070 during the 2018 outburst in its hard state from MJD58,190 to 58,289 with Insight-HXMT in a broad energy band 1-150 keV. We find different behaviors of the hardness ratio, the fractional rms and time lag before and after MJD58,257, suggesting a transition occurred around this point. The observed time lags between the soft photons in the 1-5 keV band and the hard photons in higher energy bands, up to 150 keV, are frequency-dependent: the time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
7
41
2
Order By: Relevance
“…MAXI J1820+070 is one of the brightest BHBs detected so far, and has exhibited a great amount of activity in radio (Bright et al 2020;Homan et al 2020), NIR (Sánchez-Sierras & Muñoz-Darias 2020), optical (Muñoz-Darias et al 2019;Paice et al 2019;Shidatsu et al 2019;Veledina et al 2019), ultraviolet (UV; Kajava et al 2019), and X-ray (Buisson et al 2019;Kara et al 2019;Espinasse et al 2020;Wang et al 2020b;Buisson et al 2021;You et al 2021;Zdziarski et al 2021). In the hard state, reverberation analysis using the Neutron Star Interior Composition Interior Explorer (NICER; Gendreau et al 2016) showed that while the broad iron line profile remained constant (and only the narrow component decreased), the frequency range where the (soft) reverberation lag dominated increased (Kara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MAXI J1820+070 is one of the brightest BHBs detected so far, and has exhibited a great amount of activity in radio (Bright et al 2020;Homan et al 2020), NIR (Sánchez-Sierras & Muñoz-Darias 2020), optical (Muñoz-Darias et al 2019;Paice et al 2019;Shidatsu et al 2019;Veledina et al 2019), ultraviolet (UV; Kajava et al 2019), and X-ray (Buisson et al 2019;Kara et al 2019;Espinasse et al 2020;Wang et al 2020b;Buisson et al 2021;You et al 2021;Zdziarski et al 2021). In the hard state, reverberation analysis using the Neutron Star Interior Composition Interior Explorer (NICER; Gendreau et al 2016) showed that while the broad iron line profile remained constant (and only the narrow component decreased), the frequency range where the (soft) reverberation lag dominated increased (Kara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up X-ray observations since its outburst were carried out by other X-ray telescopes, e.g., Swift 22 , NuSTAR 23 , and NICER 24 . The long-term and high cadence observation of MAXI J1820 + 070 by Hard X-ray Modulation Telescope (called Insight-HXMT) 25 was carried from 2018-03-14 (MJD 58191) to 2018-10-21 (MJD 58412) 26 . Figure 1 shows the Insight-HXMT HE (red)/ME (blue)/LE (green) light curves (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray transients spend most of their lives in a quiescent state but show bright outbursts lasting for weeks to months with a recurrence time varying from months to decades (Tanaka & Shibazaki 1996;Chen et al 1997;Tomsick & Kaaret 2000). Compared to supermassive black holes, stellar-mass black holes display much richer and faster variability and thus provide an ideal window to study the evolution of extreme astrophysical phenomena, such as accretion and ejection processes, in an observable timescale (e.g., Shakura & Sunyaev 1973;Poutanen & Fabian 1999;Belloni et al 2000;Uttley et al 2005Uttley et al , 2014Altamirano & Méndez 2015;Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%